Pendampingan UKM dalam Pengurusan Izin Usaha dan Penerapan Manajemen Modern untuk Peningkatan Daya Saing di Desa Keruak - Yuniar Affandy; Salmi Yuniar Bahri; Masbullah Masbullah; Bahrian Yodik Firman; Dadang Kurniawan Saputra (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2024)
This study aims to analyze the effectiveness of assistance provided to Small and Medium Enterprises (SMEs) in business licensing and the implementation of modern management practices in Keruak Village. The method used involves a qualitative approach through in-depth interviews and participatory observation. The results indicate that the assistance has improved the understanding and capabilities of SME actors in managing business permits and applying modern management principles. This has had a positive impact on enhancing the competitiveness of SMEs in both local and regional markets. The study recommends the need for a sustainable and integrated assistance program to ensure the continued development of SME capacity.